Elucidation of the mechanism of atorvastatin-induced myopathy in a rat model. (1st June 2016) - El-Ganainy, Samar O.; El-Mallah, Ahmed; Abdallah, Dina; Khattab, Mahmoud M.; Mohy El-Din, Mahmoud M.; El-Khatib, Aiman S.
Abstract: Myopathy is among the well documented and the most disturbing adverse effects of statins. The underlying mechanism is still unknown. Mitochondrial dysfunction related to coenzyme Q10 decline is one of the proposed theories. The present study aimed to investigate the mechanism of atorvastatin-induced myopathy in rats. In addition, the mechanism of the coenzyme Q10 protection was investigated with special focus of mitochondrial alterations. Sprague-Dawely rats were treated orally either with atorvastatin (100 mg/kg) or atorvastatin and coenzyme Q10 (100 mg/kg). Myopathy was assessed by measuring serum creatine kinase (CK) and myoglobin levels together with examination of necrosis in type IIB fiber muscles. Mitochondrial dysfunction was evaluated by measuring muscle lactate/pyruvate ratio, ATP level, pAkt as well as mitochondrial ultrastructure examination. Atorvastatin treatment resulted in a rise in both CK (2X) and myoglobin (6X) level with graded degrees of muscle necrosis. Biochemical determinations showed prominent increase in lactate/pyruvate ratio and a decline in both ATP (>80%) and pAkt (>50%) levels. Ultrastructure examination showed mitochondrial swelling with disrupted organelle membrane. Co-treatment with coenzyme Q10 induced reduction in muscle necrosis as well as in CK and myoglobin levels. In addition, coenzyme Q10 improved all mitochondrial dysfunction parameters including mitochondrial swelling and disruption. These results presented a model for atorvastatin-induced myopathy in rats and proved that mitochondrial dysfunction is the main contributor in statin-myopathy pathophysiology.